Rainfall and landslides in Karditsa county (Greece): a statistical approach - Pyrgiotis, L.; Koukis, G.; Sabatakakis, N. (Bulletin of the Geological Society of Greece, 2007)
The mountainous area of Karditsa County, being geologically a representative sample of Olonos- Pindos geotectonic zone, is characterized by rainfall- induced landslides on steep slopes of high relief. After a systematic data inventory concerning landslides and their quantitative expression, the correlation between landslide occurrence and rainfall is investigated. Following the analyses performed a close interrelation between landslides and precipitation is established. Finally, a characteristic example of rainfall- induced landslide in the wider area of the county is given